Zapin Songket Dance Choreography at The Bina Tasik Studio, Pangkalan Kerinci District - Diye Chania; Indrayuda (Universitas Negeri Padang, 2023)
The purpose of this article is to explore the choreography of Zapin Songket Pangkalan Kerinci District. This qualitative research uses a descriptive approach. The researcher herself, assisted by stationery, a telephone, and recording types, were the research instruments. To collect data, observation, interview, documentation, and literature study were used. Data collection, data reduction, data presentation, and conclusion drawing are the steps used to analyze this research. The results show that the choreographic process of Zapin Songket Dance begins with idea, theme, type, exploration, improvisation, and composition. Then it is divided into categories based on form elements: movement, floor patterns, dynamics, music, costumes, properties, and group composition. There is one choreographic work pattern with the same motion character, based on the work pattern.